Hair Growth Promoting Activity of Zauberöl® in Testosterone-Induced Alopecia in Wistar Rats (Advancements in Homeopathic Research, 2023)
Background: Hair loss, or alopecia, is a common  disorder that affects between 0.2-2% of the world's  population and have significant impacts on a person's  mental and physical health. Normal hair loss on  a healthy head is between 50 and 100 hairs a day.  Alopecia is a disorder in which the follicles in certain  people start losing hair prematurely because they are  not healthy, increasing the pace at which hair falls.  Alopecia can be caused by poor nutrition, chronic  stress, genetics, or other factors, and there are several  types, each with a unique cause and symptom. Apart  from improving quality of life, using methods like hair  treatments or transplants, many homeopathic herbal  ingredients are reported useful in managing alopecia  and hair fall. This study was aimed to investigate the  effectiveness of a formulation Zauberӧl® containing  Arnica montana, Ceanothus americanus, Eclipta  prostrata, Hibiscus Rosa sinensis, Jaborandi, Murraya  koenigii, Sabal serrulata & Thuja occidentalis in  testosterone-induced alopecia in Wistar rats.
Keywords: Alopecia; Zauberӧl®; hair oil; hair fall